Peningkatan Citra Pada Sekolah-Sekolah Yayasan Pendidikan XYZ di Jawa Timur - Monica Adjeng; Veronica Rahmawati; Marliana Junaedi; Fenika Wulani (Jurnal Abdimas Perbanas, 2023)
The image can be determined by quality, promotion and interaction with the client. In this case, the teacher is the one that has a role in the image of the school. The Yohanes Gabriel Foundation, which manages 140 schools, has difficulty in implementing strategic promotional policies often varying for each of the schools under its management. This of course requires different strategies.  In addition, the existence of schools in different regions with various characteristics is also a problem for Yohanes Gabriel administrators to make policies that can be used to solve promotional problems and foster long-term relationships with stakeholders. Thus, training will improve and maintain an image becomes a necessity. The Abdimas team will help Yohanes Gabriel by conducting a problem survey as a first step to sharpen the direction of the training. Furthermore, the training focuses on improving the school's image with the topics of personal branding, promotion, and customer relationship management (CRM). From the results of this activity, it can be concluded that schools under Yohanes Gabriel have the main problems faced, namely a decrease in the number of students and the ineffective use of social media. This is due to the limited human resources and the ability to manage and utilize social media as one of the effective promotional tools for school introduction.